The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ajpath.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Endothelial Regeneration and Vascular Repair and Their Application to Regenerative Medicine

Abstract: Endothelial barrier integrity is required for maintaining vascular homeostasis and fluid balance between the circulation and surrounding tissues and for preventing the development of vascular disease. Despite comprehensive understanding of the molecular mechanisms and signaling pathways mediating endothelial injury, the regulatory mechanisms responsible for endothelial regeneration and vascular repair are incompletely understood and constitutes an emerging area of research. Endogenous and exogenous reparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 97 publications
0
63
0
Order By: Relevance
“…Although it may appear surprising that the maximal FMD change was observed after the end of the treatment period, repair of dysfunctional endothelium is considered to be a gradual process taking weeks and includes restoring endothelial junctions, barrier integrity and overall endothelial regeneration. 70 As the effect appeared to be both time-and dose-dependent, it is difficult to conclude whether the maximal possible effect of SAR247799 on FMD was reached. However, as SAR247799 was at least as effective as sildenafil under the conditions evaluated, a level of clinical relevance of the S1P 1 mechanism has been established that warrants further evaluation in patients, including settings with longer treatment duration and/or with more relevant clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Although it may appear surprising that the maximal FMD change was observed after the end of the treatment period, repair of dysfunctional endothelium is considered to be a gradual process taking weeks and includes restoring endothelial junctions, barrier integrity and overall endothelial regeneration. 70 As the effect appeared to be both time-and dose-dependent, it is difficult to conclude whether the maximal possible effect of SAR247799 on FMD was reached. However, as SAR247799 was at least as effective as sildenafil under the conditions evaluated, a level of clinical relevance of the S1P 1 mechanism has been established that warrants further evaluation in patients, including settings with longer treatment duration and/or with more relevant clinical endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…ECs are normally quiescent with a very low turnover rate. In response to injury, expression of some transcriptional factors is induced to activate EC proliferation (42). We have shown previously that FoxM1 is markedly induced in lung ECs in the recovery phase but not in the injury phase in young adult mice following LPS challenge (27).…”
Section: Discussionmentioning
confidence: 96%
“…Re-endothelialization is a complex mechanobiological process, which is modulated by the proliferation and migration of resident endothelial cells from uninjured intima ( Evans et al, 2020 ; Li et al, 2021 ) and by the adhesion of circulating endothelial cells ( Tesfamariam, 2016 ; Hu et al, 2019 ). Increased circulating endothelial cells in the peripheral blood have been reported in various pathologic conditions involving severe endothelial perturbation, including inflammatory disease, acute myocardial infarction, unstable angina, and critical limb ischemia ( Makin et al, 2004 ; Lee et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since endothelial progenitor cells (EPCs) were found in peripheral blood, circulating EPCs were regarded as the primary cell source for reconstructing the damaged endothelium ( Zhang et al, 2014 ). On the other hand, mounting evidence indicated that circulating EPCs (most likely monocytic) could not directly contribute to endothelial regeneration by forming part of the regenerating endothelium ( Evans et al, 2020 ). As a marker of endothelial injury, circulating endothelial cells detached from impaired vessels, sloughed into the circulation, and contributed to vascular repair ( Quilici et al, 2004 ; Blann et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%